Elevated troponin levels in patients with atrial tachyarrhythmias. Issue 5 (August 2020) - Rozenbaum, Zach; Sapir, Orly; Taieb, Philippe; Ziv-Baran, Tomer; Konigstein, Maayan; Hochstadt, Aviram; Rosso, Raphael; Banai, Shmuel; Chorin, Ehud
Abstract : Objective: Data regarding the significance of elevated troponin in the setting of atrial tachyarrhythmia remain inconclusive. In the present study, we aimed to explore the discriminative ability of troponin for obstructive coronary artery disease (CAD) among patients with atrial tachyarrhythmias. Methods: We retrospectively identified patients with atrial tachyarrhythmias and elevated serum troponin levels, who underwent invasive coronary angiography during the same admission. The prevalence of obstructive CAD among these patients was compared to that of historically matched patients who underwent coronary angiography due to suspected non-ST elevation myocardial infarction and had no arrhythmias. Results: Overall 318 patients with suspected non-ST elevation myocardial infarction were analyzed ( n = 159 with atrial tachyarrhythmias and n = 159 without arrhythmias). Obstructive CAD was detected in 39% of patients with an arrhythmia compared to 85.5% in the control group ( P < 0.001). A multivariable analysis demonstrated that parameters associated with obstructive CAD among patient with atrial tachyarrhythmias and elevated troponin were diabetes mellitus [odds ratio (OR) 2.7, 95% confidence interval (CI) 1.23–5.91, P = 0.013], prior ischemic heart disease (OR 4.48, 95% CI 1.93–10.4, P < 0.001) and troponin level (OR 3.18 for every 1000 ng/L increment, 95% CI 1.85–5.48, P < 0.001). Conclusions: Elevated troponin is not a reliable indicator for the presence of underlying obstructive CAD among patients who present with atrial tachyarrhythmias. Risk stratification of these patients should rely on the degree of troponin elevation, and the presence of diabetes mellitus and prior ischemic heart disease. Abstract : Supplemental Digital Content is available in the text.